Potensi Daya Inhibisi Ekstrak Etanol Daun Sirih Merah (Piper crocatum Ruiz & Pav) Terhadap Mikroorganisme Pada Biofilm Di Pelat Gigi Tiruan Berbahan Hot Curing Acrylic - Susanna Halim; Gusbakti Rusip; Siti Farah Syarbaini (Postgraduate, University of Mataram, 2025)
Tooth loss reduces quality of life by affecting chewing and speech function and can interfere with social activities. Hot curing acrylic dentures have the disadvantage of high porosity and surface roughness, so they are susceptible to food residues and microorganisms that can lead to the formation of biofilm and denture stomatitis. Red series leaves (Piper crocatum Ruiz & Pav) have chemical content such as flavonoids, alkaloids, and essential oils that have the potential to be antimicrobials. This study aims to determine the potential of red betel leaf ethanol extract in inhibiting microorganisms in biofilms in denture plates made of hot curing acrylic. This study used the liquid dilution method to test the effectiveness of red betel leaf ethanol extract with concentrations of 10%, 25%, 50% and 75% on the growth of Streptococcus mutans, Lactobacillus acidophilus, and Candida albicans contaminated on round denture plates made of hot curing acrylic. The results showed that the ethanol extract of red betel leaf significantly reduced the number of bacterial and fungal colonies, with a concentration of 75% showing the highest effectiveness, especially against the bacterium Lactobacillus acidophilus with an average colony count of 45.67 ± 4.04. Red betel leaf ethanol extract contains chemical compounds that are effective as antimicrobials in biofilms in denture plates made of hot curing acrylic. This extract has the potential to be an alternative natural ingredient for denture cleaning.